DETERMINATION OF FLOOD DISCHARGE OF MOYAN WEIR WITH HEC-RAS PROGRAM - Achmad Syarifudin (Asosiasi Peneliti Sriwijaya, 2022)
This research was conducted to obtain the right discharge plan in the irrigation area with a study of the amount of discharge that can be used upstream of the weir so that the water supply at the intake does not lack water. The Deras II Irrigation Area covering an area of 928 hectares, has 2 weirs as a source of irrigation water, namely the Moyan weir and Aur Weir. The upstream part of the Moyan weir is a sleeping area in the form of a swamp which farmers use to become a paddy field whose source of water comes from the swift river (upstream Moyan weir). With this water uptake, the impact on the flow of water entering the Moyan intake will be reduced, so it needs to be done with the numerical method approach of the HEC-RAS program. The results of this study are graphically depicted at each review station in the channel and the existing discharge obtained from the measurement of the speed with the current meter and water level from each cross-section along the irrigation channel. The simulation results are obtained with the condition of the river crossing, which is not filled, and the discharge is 0.024 m3/sec. The water level at the downstream cross-section is filled as high as 75 cm with a flow velocity of 0.783 m/sec, and the water level downstream of the irrigation channel is as high as 40 cm.